Exploration of the Opinions of Mphil Students for Online Education During COVID-19 Pandemic - Zain Ul Islam Adil; Sidra Rizwan (JELM, 2023)
The outbreak of COVID-19 has had a significant impact on the educational system around the world; it has forced the closure of educational institutions, which has a negative impact on the student fraternity around the world. COVID-19 required containment and enforced isolation because of its contagious nature, which had a significant impact on teacher-student interactions. Computer-based learning has emerged as the closest equivalent for offline instruction in the absence of traditional classroom teaching and one-to-one engagement. In light of this, it is important to investigate students' perceptions and preparation for the online learning system being implemented at the university level during the ongoing COV. In light of this, it's important to look into students' perceptions and readiness for the online learning system that has been implemented at the university level during the ongoing COVID-19 pandemic. The quantitative approach was used in this study, and responses were collected via an online questionnaire. In the year 2020, a research study was undertaken. The study's findings demonstrate students' positive attitudes regarding elearning and, as a result, their acceptance of this new learning system. It has also proved the value of e-learning in the context of the COVID-19 problem. E-learning has evolved as a new technique for increasing the learning process, with social media potentially enhancing the learning output even further. The study's findings will help educational institutions and policymakers take online learning toward the next stage in a more effective way.